Low-field 14N nuclear magnetic resonance for detection of dangerous liquids - Mozzhukhin, G., V; Kupriyanova, G., V; Mamadazizov, S. Sh; Marasli, A.; Rameev, B. Z. (Elsevier Science Bv, 2018)
The T-1 and T-2 relaxation times of some nitrogen-containing liquids were measured by N-14 pulse nuclear magnetic resonance (NMR) in the magnetic field of 0.575 T. The liquids measured in this paper were energetic and toxic substances as well as some electrolytes. A method of the fast discrimination of dangerous liquids by the low field N-14 NMR relaxation parameters was proposed. It is shown that flammable and toxic nitrogen-based liquids have small values of T-1 and T-2, therefore these liquids may be discriminated from the group of less dangerous liquids.
Keywords: Nuclear magnetic resonance (NMR); N-14 NMR relaxation; Detection of energetic and dangerous liquids